Comparative transcriptomic analysis-based identification of the regulation of foreign proteins with different stabilities expressed in Pichia pastoris - Niu, Tingting; Cui, Yi; Shan, Xu; Qin, Shuzhen; Zhou, Xuejie; Wang, Rui; Chang, Alan; Ma, Nan; Jing, Jingjing; He, Jianwei (Frontiers in Microbiology, 2022)
Introduction The industrial yeast Pichia pastoris is widely used as a cell factory to produce proteins, chemicals and advanced biofuels. We have previously constructed P. pastoris strains that overexpress protein disulfide isomerase (PDI), which is a kind of molecular chaperone that can improve the expression of an exogenous protein when they are co-expressed. Chicken cystatin (cC) is a highly thermostable cysteine protease inhibitor and a homologous protein of human cystatin C (HCC). Wild-type cC and the two mutants, I66Q and ΔW (a truncated cC lacking the á-helix 2) represent proteins with different degrees of stability. Methods Wild-type cC, I66Q and ΔW were each overexpressed in P. pastoris without and with the coexpression of PDI and their extracellular levels were determined and compared. Transcriptomic profiling was performed to compare the changes in the main signaling pathways and cell components (other than endoplasmic reticulum quality control system represented by molecular chaperones) in P. pastoris in response to intracellular folding stress caused by the expression of exogenous proteins with different stabilities. Finally, hub genes hunting was also performed. Results and discussion The coexpression of PDI was able to increase the extracellular levels of both wild-type cC and the two mutants, indicating that overexpression of PDI could prevent the misfolding of unstable proteins or promote the degradation of the misfolded proteins to some extent. For P. pastoris cells that expressed the I66Q or ΔW mutant, GO (Gene Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) analyses of the common DEGs in these cells revealed a significant upregulation of the genes involved in protein processing, but a significant downregulation of the genes enriched in the Ribosome, TCA and Glycolysis/Gluconeogenesis pathways. Hub genes hunting indicated that the most downregulated ribosome protein, C4QXU7 in this case, might be an important target protein that could be manipulated to increase the expression of foreign proteins, especially proteins with a certain degree of instability. Conclusion These findings should shed new light on our understanding of the regulatory mechanism in yeast cells that responds to intracellular folding stress, providing valuable information for the development of a convenient platform that could improve the efficiency of heterologous protein expression in P. pastoris.